Comparison of long-acting injectable antipsychotics with oral antipsychotics and hospital readmission rates in pediatric patients - Danial Chowdhury, PharmD; Daniel Greer, PharmD, BCPP; Mei T. Liu, PharmD, BCPP; Caitlin McCarthy, PharmD, BCPP; Megan Maroney, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2024)
Introduction Studies indicate that long-acting injectable antipsychotics (LAIAs) reduce the risk of relapse and hospitalization compared with oral antipsychotics (APs) in adults. Oral formulations of APs are well-studied in the pediatric population, but little is known regarding the off-label use of LAIAs in this population. Methods This retrospective chart review evaluated readmission rates for pediatric patients admitted to a psychiatric ward in a large academic hospital between January 1, 2015, and December 1, 2022, requiring AP therapy. The experimental group included patients initiated on LAIA therapy, and the control group included patients initiated on a new oral AP. Patients were matched by several clinical factors. Results Each group consisted of 38 patients. For the primary outcome, hospital readmission rates at 3 months, the LAIA group had a 13.2% readmission rate compared with 26.3% in the comparator group (p = .153). In months 4 through 6, there was a 5.3% versus 15.8% readmission rate, respectively (p = .139). In months 7 through 12, it was 7.9% versus 18.4% (p = .179). There were significantly fewer cumulative readmissions at the 1-year mark in the LAIA group (N = 9, 23.7%) compared with the oral AP group (N = 18, 47.4%) (p = .031). No statistically significant differences were seen in hospital length of stay although results numerically favored LAIA. Discussion In a pediatric population, the administration of an LAIA when compared with the oral equivalent resulted in numerically fewer hospital readmissions, decreased length of stay, and fewer adverse effects, but these effects were not statistically significant except for cumulative readmissions at 1 year.